Three-Dimensional Determination of the Fusion Zone between the Distal Maxilla and the Pterygoid Plate of the Sphenoid Bone and Considerations for Implant Treatment Procedure - Stefan Ihde; Łukasz Pałka; Sławomir Jarząb; Maciej Janeczek; Karolina Goździewska-Harłajczuk; Joanna Klećkowska-Nawrot; Izabela Janus; Maciej Dobrzyński (Applied Sciences, 2020)
During pre-operation planning, an implantologist has to decide about the location of a dental implant based on the available bone, anatomical structures and future prosthetics. The aim of this study was to provide an overview of the configurations of the junction zone of the pterygoid process, maxillary tuberosity and pyramidal process among the population and to determine the usefulness of 3D model visualization in regard to precision of anatomical structure projections for clinical planning. A total of 72 cases were analyzed for seven measurements (lateral, medial, rostral, caudal, area, line-1 longitudinal, line-2 transverse) on both body sides—right (R) and left (L). In 57 cases, age and sex of the patient were given. In 15 cases this information was missing. Among the group of 57 cases with complete data, there were 30 females (F) and 27 males (M). A total of 57 models of upper jaws including the adjacent pterygoid process of the sphenoid bone were taken for investigation. The results of the comparison between the right and left side showed no differences (p > 0.05) in values of the measured parameters. The results of the comparison between males and females showed a statistically significant difference when assessing the line-2 transverse (p < 0.05)—in the male group the average was 8.22 mm, in the female group the average was lower (7.83 mm). No statistically significant differences in values of the measured parameters for females and males were found for the left side nor for the right side. In all examined specimens there was enough bone surface in the fusion zone to allow for the stable placement of one tuberopterygoid implant.